Logistic Regression Analysis of Mode of Delivery Influencing Nutritional Status among Under-Five Children in Bangladesh: Survey in Rural Area of Rajshahi District (International Journal of Statistical Sciences, 2023)
Caesarean delivery is a surgical procedure in which a fetus is delivered through an incision in the mother's abdomen and uterus. If there are no complications with women pregnancy or labor, a vaginal birth is safer than a caesarean birth. Worldwide the rates of C-section have gradually increased in the latest decades. The aim of the study was to determine the prevalence of caesarian delivery, and to investigate the impact of caesarian delivery on nutritional status of under-five children in the rural area of Rajshahi district, Bangladesh. This was a cross sectional study. Data was collected from Rajshahi district using multistage sampling. A total number of 540 mothers having at least one under-five children currently living together were considered. In order to data analysis, descriptive statistics, Z-proportional test and both univariable and multivariable logistic regression models were in this study according to our objectives. This study revealed that the prevalence of caesarian delivery among mothers living in the rural area of Rajshahi, Bangladesh was 34.4%. The prevalence of stunting, underweight and wasting among under-five children were 43.70%, 39.63% and 27.96% respectively. The stunting, underweight and wasting under-five children were 32.6%, 28.0% and 29.1%  respectively who were born by caesarian delivery,  these were significantly (p